Respuesta :
This looks like a 2 step equation, so here's what we'll do:
1) We need to isolate our variable, so we're going to subtract 6z from both sides. This is a special case where our variables' coefficients have the same value, so they will cancel out.
3+6z=13+6z
- 6z - 6z
3=13
2) We are left with... 3=13. We're going to subtract 3 from both sides to get this:
3=13
- 3 - 3
0=13
3) We see that our answer is 0=13, but we know that 0 cannot equal 13! So, since we cannot simplify any further, our answer will come out to be...
NO SOLUTION.
The reason we get [NO SOLUTION] as our answer is because we were originally trying to get a value for our variable. However, the variable does not have a value, so since there is no value for our variable, there is no solution.
1) We need to isolate our variable, so we're going to subtract 6z from both sides. This is a special case where our variables' coefficients have the same value, so they will cancel out.
3+6z=13+6z
- 6z - 6z
3=13
2) We are left with... 3=13. We're going to subtract 3 from both sides to get this:
3=13
- 3 - 3
0=13
3) We see that our answer is 0=13, but we know that 0 cannot equal 13! So, since we cannot simplify any further, our answer will come out to be...
NO SOLUTION.
The reason we get [NO SOLUTION] as our answer is because we were originally trying to get a value for our variable. However, the variable does not have a value, so since there is no value for our variable, there is no solution.